Audit on the Use of Dangerous Abbreviations, Symbols, and Dose Designations in Paper Compared to Electronic Medication Orders: A Multicenter Study. Issue 4 (April 2018) - Cheung, Stephanie; Hoi, Sannifer; Fernandes, Olavo; Huh, Jin; Kynicos, Sara; Murphy, Laura; Lowe, Donna
Background: Dangerous abbreviations on the Institute for Safe Medication Practices Canada's "Do Not Use" list have resulted in medication errors leading to harm. Data comparing rates of use of dangerous abbreviations in paper and electronic medication orders are limited.Objective: To compare rates of use of dangerous abbreviations from the "Do Not Use" list, in paper and electronic medication orders. Secondary objectives include determining the proportion of patients at risk for medication errors due to dangerous abbreviations and the most commonly used dangerous abbreviations.Methods: One-day cross-sectional audits of medication orders were conducted at a 6-site hospital network in Toronto, Canada, between December 2013 and January 2014. Proportions of paper and electronic medication orders containing dangerous abbreviation(s) were compared using a χ 2 test. The proportion of patients with at least 1 medication order containing dangerous abbreviation(s) and the top 5 dangerous abbreviations used were described.Results: Overall, 255 patient charts were reviewed. The proportions of paper and electronic medication orders containing dangerous abbreviation(s) were 172/714 (24.1%) and 9/2207 (0.4%), respectively ( P < 0.001). Almost one-third of patients had medication order(s) containing dangerous abbreviation(s). The proportions of patients with at least 1 medication order during the audit period containing dangerous abbreviation(s) for patients with paper only, electronic only, or a hybrid of paper and electronic medication orders were 50.5%, 5%, and 47.2%, respectively. Those most commonly used were "D/C", drug name abbreviations, "OD, " "cc, " and "U."Conclusions: Electronic medication orders have significantly lower rates of dangerous abbreviation use compared to paper medication orders.